The Night Guest - McFarlane, Fiona 1978- (New York : Faber and Faber, Inc., an affiliate of Farrar, Straus and Giroux, 2013)
"An elderly Australian woman lets a mysterious and possibly sinister caretaker into her beach-side home and into her life"--
Keywords: Widows -- Fiction; Caregivers -- Fiction; FICTION / Literary; Australia -- Fiction; Suspense fiction